2002
DOI: 10.1152/ajpheart.00656.2001
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates migration of retinal microvascular pericytes: involvement of TGF-β and PDGF-BB

Abstract: We studied the promigratory effect of angiotensin II (ANG II) on cultured bovine retinal microvascular pericytes. ANG II stimulated migration of pericytes by 86% at 10(-8) M, but this effect was lost at 10(-4) M. Migratory responses were inhibited by the ANG II type 1 (AT(1)) receptor antagonist losartan but not by PD-123319, an AT(2) antagonist. Addition of PD-123319 to the 10(-4) M ANG II dose restored migratory responses. The promigratory effect of ANG II (10(-7) M) was reduced by 59% in absence of gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…A previous in vitro study has reported PD123319 to not attenuate ANG II-stimulated retinal pericyte migration. 12 In the present study, we found in both sham and untreated ROP rats, that both AT1 and AT2 receptors were localized not only to blood vessels but also to the ILM and nuclei in the INL, which presumably represent macroglial Muller cells. Importantly, Muller cells are associated with retinal blood vessels 47 and are sites of VEGF and VEGF-R2 expression.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A previous in vitro study has reported PD123319 to not attenuate ANG II-stimulated retinal pericyte migration. 12 In the present study, we found in both sham and untreated ROP rats, that both AT1 and AT2 receptors were localized not only to blood vessels but also to the ILM and nuclei in the INL, which presumably represent macroglial Muller cells. Importantly, Muller cells are associated with retinal blood vessels 47 and are sites of VEGF and VEGF-R2 expression.…”
Section: Discussionsupporting
confidence: 53%
“…[1][2][3] There is accumulating evidence that angiotensin II (ANG II), the effector peptide of the renin-angiotensin system (RAS), is a key pathophysiological factor in a number of retinal vascular disorders including ROP and PDR. 4 -7 In addition to its well characterized hemodynamic actions, ANG II is also a growth factor, stimulating endothelial and smooth muscle cell proliferation, 8 -10 pericyte migration, 11,12 and smooth muscle cell hypertrophy. 13 The actions of ANG II are largely mediated by two receptors; angiotensin type 1 (AT1) and angiotensin type 2 (AT2).…”
mentioning
confidence: 99%
“…In contrast, selective inhibition of each pathway displayed similar effects on NADPH oxidase, CuZn-SOD and NOS activities. The similarities in these responses can in part be explained by the well-documented presence of a cross-talk between G-protein coupled AT 1 R and the PDGF receptor tyrosine kinase in vascular SMCs and thus the ability of Ang II to elicit responses unique to growth factor stimulation [15,16,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent data have implicated PDGF-BB in Ang II-induced chemotaxis and revealed the ability of Ang II to activate PDGF- receptor [15,16]. Taken these close functional interactions into account, the present study examined whether mechanistic dis/similarities exist between these atherogens to trigger vascular pathologies.…”
Section: Introductionmentioning
confidence: 96%
“…22 It is possible that VEGF signaling is not completely blocked by endostatin. However, other factors, like IGF-1, TGF B and PDGF, 23,24 contribute to retinal neovascularization in ischemic retinopathies and could be responsible for residual angiogenesis. Indeed, Ozaki et al 25 have totally inhibited retinal neovascularization in the same mouse model of retinal neovascularization by using a kinase inhibitor that targets VEGF and PDGF receptors.…”
Section: Discussionmentioning
confidence: 99%